ANALISIS PERANCANGAN ALAT BANTU MATERIAL HANDLING PRODUKSI GENTENG MENGGUNAKAN METODE AXIOMATIC HOUSE OF QUALITY (AHOQ) - Muhammad Dian Putra; Ishardita Pambudi Tama; Debrina Puspita Andriani (Journal of Engineering and Management in Industrial System, 2016)
IKM genteng Talangsuko is a roof tile producers that was founded in 1980. They can produce 300-350 roof tile in each day. However, the accumulation of material happens frequently due to the limited capacity of drying space. This problem causes the production process to be obstructed, so they need an equipment that can increase the production capacity of the roof tile. Accordingly, the purpose of this research are to determine the design and spesification of the equipment and to determine whether the equipment could increase the production capacity of roof tile. This rearch proposes design of the equipment using the AHOQ method. The result of this research is the specification of the equipment that consist of three components which are rack body, wheels, and the last part is slope arranger for each level of rack. The design of material handling equipment is in the form of multilevel racks with wheels. This equipment may increase the production capacity of roof tile in IKM Genteng Talangsuko especially for the drying process to 2 times from 300-350 to ± 750 roof tiles.